2014
DOI: 10.1007/s00520-014-2227-y
|View full text |Cite
|
Sign up to set email alerts
|

Are orange lollies effective in preventing nausea and vomiting related to dimethyl sulfoxide? A multicenter randomized trial

Abstract: This is the author's final version of the contribution published as: Gonella S; Berchialla P; Bruno B; Di Giulio P.. Are orange lollies effective in preventing nausea and vomiting related to dimethyl sulfoxide? A multicenter randomized trial. SUPPORTIVE CARE IN CANCER. 22 (9) ConclusionThe vasoconstrictive action of ice may prevent NV related to DMSO in the acute phase and reduce the need for rescue anti-emetic therapy. Ice lollies offer a simple, non-invasive and economic means for relieving nausea and vomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
8
0
3
Order By: Relevance
“…The effects of orange aroma are yet to be elucidated. Some previous studies have indicated that orange aroma has psycho‐physiological benefits , but several others have failed to support these assertions . The literature indicates that orange aroma may not be beneficial for stress reduction, and in some cases may even lead to increased stress.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of orange aroma are yet to be elucidated. Some previous studies have indicated that orange aroma has psycho‐physiological benefits , but several others have failed to support these assertions . The literature indicates that orange aroma may not be beneficial for stress reduction, and in some cases may even lead to increased stress.…”
Section: Introductionmentioning
confidence: 99%
“…The study reporting the highest incidence of nausea had a follow-up period of 5 days 48 , and the authors concluded that the high incidence of nausea observed might be due to the long follow-up period 48 . In another article using the same data 119 , it was suggested that the delayed nausea was due to gastrointestinal mucosal damage, and only the initial nausea could be related to DMSO, and therefore we decided only to include the data from the first 2 days after infusion 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Several odor‐masking strategies have been explored, but data are conflicting (Prior et al, ; Ozdemir et al, ; Potter et al, ; Ndao et al, ). Our recent study (Gonella et al, ) of 69 auto‐HCT patients showed that, although an orange aroma administered as ice lollipops appears to damper the taste of the cryopreservative and the associated nausea, the benefit was due to the cooling rather than the aroma.…”
mentioning
confidence: 94%